Psychological contract breach and its influence on employee perception of organizational justice. - Omar, Zoharah; Abdul Rahman, Rahma Jamiah (2011)
This study was conducted to examine the occurrence of psychological breach and its influence on employee perception of organizational justice measured by distributive justice, procedural justice, and interactive justice. Data were collected from a convenience sample of 70 employees in the management and non-management category from a newspaper organization. The result showed that psychological contract breach occurred mostly at moderate and low level. The result also revealed that psychological contract breach has a significant negative influence on and distributive justice, procedural justice, and interactional justice. Several study implications were discussed and suggested in this study.